Social Interaction Patterns of Former Indonesian Female Migrant Workers: The Role of Cultural Adaptation and Social Conflict in Community Reintegration - Nunun Nurhajati (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
The large population but not linear with the number of job opportunities and not accompanied by the level of education of the community gives rise to the phenomenon of the high number of migrant workers in Indonesia, especially female migrant workers. Social conflicts often arise when these migrant workers return to their homeland and interact with their environment. The existence of cultural differences and living habits makes changes in the lifestyle of migrant workers create friction of interests between communities when they interact. The purpose of this study is to analyze the impact of social interaction patterns of former female migrant workers who bring positive or even negative values to their environment and the differences with women who have never been migrant workers along with the factors that influence these social interaction patterns. The method used is a qualitative descriptive research method where researchers obtain data through observation, interviews and documentation. Data analysis uses data collection, data reduction, data presentation and drawing conclusions. Based on field research, it was found that these female former migrant workers have different interaction patterns from women who have never worked as migrant workers which can be seen from the way they behave and respond to a problem. Female former migrant workers have more open thinking even though they also become individualists which ultimately causes social conflict in their environment. There are several factors that influence including: communication, differences in perspective or mindset and also habits so that it takes time to re-adapt to the culture and interaction patterns with the local community so as not to cause social conflict in the community.Jumlah penduduk yang besar, namun tidak sebanding dengan jumlah lapangan pekerjaan dan tidak diimbangi dengan tingkat pendidikan masyarakat, menimbulkan fenomena tingginya jumlah pekerja migran di Indonesia, terutama pekerja migran perempuan. Konflik sosial sering muncul ketika para pekerja migran ini kembali ke tanah air dan berinteraksi dengan lingkungan sekitar. Perbedaan budaya dan kebiasaan hidup menyebabkan perubahan gaya hidup pekerja migran yang menimbulkan gesekan kepentingan antara masyarakat saat berinteraksi. Tujuan dari penelitian ini adalah untuk menganalisis dampak pola interaksi sosial mantan pekerja migran perempuan yang membawa nilai positif maupun negatif bagi lingkungan mereka serta perbedaan dengan perempuan yang tidak pernah menjadi pekerja migran, beserta faktor-faktor yang mempengaruhi pola interaksi sosial ini. Metode yang digunakan adalah metode penelitian deskriptif kualitatif, di mana peneliti memperoleh data melalui observasi, wawancara, dan dokumentasi. Analisis data menggunakan teknik pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan penelitian lapangan, ditemukan bahwa mantan pekerja migran perempuan ini memiliki pola interaksi yang berbeda dari perempuan yang tidak pernah bekerja sebagai pekerja migran, yang terlihat dari cara mereka berperilaku dan merespons suatu masalah. Mantan pekerja migran perempuan cenderung memiliki pola pikir yang lebih terbuka meskipun juga menjadi individualis, yang pada akhirnya menyebabkan konflik sosial di lingkungan mereka. Beberapa faktor yang mempengaruhi termasuk komunikasi, perbedaan perspektif atau pola pikir, dan kebiasaan, sehingga dibutuhkan waktu untuk beradaptasi kembali dengan budaya dan pola interaksi di masyarakat lokal agar tidak menimbulkan konflik sosial di komunitas tersebut.